The effect of seeding date, seeding rate and N fertilization on winter wheat yield and yield components in eastern Newfoundland - Spaner, D.; Todd, A. G.; McKenzie, D. B. (Canadian Journal of Plant Science, 2000)
Livestock farmers in Newfoundland presently import most of their feed grain, and local self-sufficiency in grain production is a desirable long-term goal. The overall objective of this work was to refine our understanding of winter wheat (Triticum aestivum L.) production in Newfoundland, with the aim of improving present cropping recommendations. We conducted trials near St. John's in 1998 and 1999 to examine the effect of seeding rate and topdress ammonium nitrate (N) fertilization rate on Borden winter wheat yield and yield components. We also conducted four seeding date trials in the same region. Optimum-treatment grain yields in our six trials ranged from 2.76 to 5.39 t ha −1 . In years of variable winter kill, increasing seeding rate up to 450 seeds m −2 increased spikes m −2 at harvest, resulting in increased grain yield. Seeding rate, however, was not as important as N fertilization in maximizing grain yield. Increasing topdress fertilization to 60 kg N ha –1 increased spikes m –2 at harvest in years of variable winter kill, resulting in greater grain yield. In years of high winter survival, the main source of higher grain yield levels (through higher N application rates) was not achieved through greater spikes m −2 at harvest, but rather through an increase in kernel weight. Optimum grain yields occurred at seeding rates of 400 ± 50 seeds m −2 , and at topdress fertilizer applications up to a rate of at least 30 kg N ha −1 . Given the results of our seeding date experiments, in conjunction with previously developed climatic models, we now consider the optimum seeding date for the eastern region of Newfoundland to be August 31. Key words: Yield component analysis, two-dimensional partitioning, Triticum aestivum L., ammonium nitrate